The Parent’s Role and Children’s Understanding of Gender Concept; A Correlational Study in Indonesia - Nurhafizah Nurhafizah; Zadrian Ardi (Journal of Counseling and Educational Technology, 2019)
The purpose of this study is to find out the extent of the relationship between the role of parents and understanding of the gender’s concepts of children in kindergartens. This research was conducted on 30 selected kindergarten students by using proportional random sampling technique. The type of this research used is quantitative research with correlation method. The populations of this study were children in Kartika 1-63 kindergarten of Padang, and the samples were children of kindergarten group B using the technique of proportional random sampling in groups B1, B2, B3, and B4. The research data was collected by using Parent Role Inventory (PRI) and Childhood Gender Concept (CGC) Inventory. The analysis of data was done validity and reliability testing and using the normality test, homogeneity test, and hypothesis test. Research data were analyzed by regression analysis. The findings of the study indicate that there is a significant correlation between the role of the parent towards the understanding of gender concepts for the children in kindergarten group B, Kartika 1 - 63 kindergarten, Padang, with correlation coefficient ry. 1 = 0564 of alpha 0.05 and Ŷ = 52, 13 + 0.445X; Based on the results of this study it can be concluded that parent have a significant role for children understanding about the concept of gender.